Boy meets girl - Spewack, Bella; Spewack, Samuel; Spewack, Bella; Spewack, Samuel (Random House, 1936)
National Theatre, George Abbott presents "Boy Meets Girl," a new play by Bella and Samuel Spewack, staged by Mr. Abbott, settings by Arne Lundborg.
Beigef.: Spewack, Bella: Spring song. Spewack, Samuel: Spring song
Keywords: Theater programs - 1936; Theater programs - Washington (D.C.)